2020
DOI: 10.3390/foods9091314
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Cryoconcentrated Calafate (Berberis microphylla) Juice during Refrigerated Storage

Abstract: This study aimed to evaluate the potential of centrifugal block cryoconcentration (CBCC) at three cycles applied to fresh calafate juice. The fresh juice and cryoconcentrate at each cycle were stored for five weeks at 4 °C and quality attributes were analyzed every 7 days. CBCC had significant effects in the calafate juice, since in the last cycle, the cryoconcentrate reached a high value of total soluble solids (TSS, ≈42 °Brix), with final attractive color, and an increase of approximately 2.5, 5.2, 5.1, 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 61 publications
8
30
3
Order By: Relevance
“…By contrast, the fresh murta juice and fresh arrayan juice increased the TTA values to 2.3 and 1.6 for C1, 3.1 and 2.1 for C2, and 3.8 and 2.6 for C3, indicating an increase in 224% and 217% (in the last cycle) in relation to the initial TTA values, respectively. The opposite behavior among pH and TTA values has been observed in various cryoconcentrated food liquids such as calafate juice [ 27 ], pineapple juice [ 42 ], and sapucaia nut cake milk [ 45 ]. The pH and TTA changes have been attributed to the continuous increases in TSS at each cycle, since it provokes an increase in the organic acids of the cryoconcentrates, causing the opposite phenomenon between pH and TTA values [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, the fresh murta juice and fresh arrayan juice increased the TTA values to 2.3 and 1.6 for C1, 3.1 and 2.1 for C2, and 3.8 and 2.6 for C3, indicating an increase in 224% and 217% (in the last cycle) in relation to the initial TTA values, respectively. The opposite behavior among pH and TTA values has been observed in various cryoconcentrated food liquids such as calafate juice [ 27 ], pineapple juice [ 42 ], and sapucaia nut cake milk [ 45 ]. The pH and TTA changes have been attributed to the continuous increases in TSS at each cycle, since it provokes an increase in the organic acids of the cryoconcentrates, causing the opposite phenomenon between pH and TTA values [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FC process at three cycles was based on the protocol described by Orellana-Palma et al [ 27 ] ( Figure 1 ). First, the plastic centrifugal tubes with 45 mL of juice were isolated with foamed polystyrene.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Lu et al [1] carried out a pilot study to investigate the changes of carotenoids, flavonoids, and vitamin C in a "Cara-Cara" juice during 16 weeks of storage at 4, 20, 30, and 40 • C. The results indicated that total flavonoids and carotenoids studied showed slight degradation at each temperature, while vitamin C degraded intensively, especially at 40 • C storage. Another work [2] also studied the bioactive compounds, antioxidant activity, and sensory analysis of a cryoconcentrated calafate (Berberis microphylla) juice during refrigerated storage. This study indicated that under a refrigerated storage time of 35 days, the cryoconcentrate samples retained bioactive compounds and the antioxidant components naturally presented in calafate juice.…”
mentioning
confidence: 99%